Pengaruh Keberanian Moral dan Modal Psikologis terhadap Efektivitas Audit Internal dengan Budaya Etis sebagai Variabel Moderasi pada Satuan Pengawas Internal PTN BLU di Indonesia - Yuyun Syafithri; Tertiarto Wahyudi; Hasni Yusrianti (Politeknik Ganesha Medan, 2026)
This study examines the influence of moral courage and psychological capital on internal audit effectiveness and investigates the moderating role of ethical culture within the Internal Audit Units (SPI) of Public Service Agency State Universities (PTN BLU) in Indonesia. Drawing on Social Cognitive Theory, this study conceptualizes moral courage and psychological capital as personal factors, while ethical culture represents an environmental factor that may shape auditors’ professional behavior. Using a quantitative approach, primary data were collected through a structured questionnaire distributed to all SPI members of 53 PTN BLU across Indonesia. A saturated sampling (census) technique was employed, resulting in 184 valid responses. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS) with SmartPLS 4. The results indicate that moral courage has a positive and significant effect on internal audit effectiveness, suggesting that auditors who uphold ethical principles and demonstrate moral firmness are more capable of conducting objective and high-quality audits. Psychological capital also shows a positive and significant effect on internal audit effectiveness, confirming that self-efficacy, optimism, hope, and resilience enhance auditors’ ability to perform under pressure. However, ethical culture does not moderate the relationship between moral courage and internal audit effectiveness, indicating that moral courage functions as an intrinsic personal attribute that operates relatively independently of organizational context. In contrast, ethical culture significantly strengthens the relationship between psychological capital and internal audit effectiveness, highlighting the importance of an ethical work environment in optimizing auditors’ psychological resources.This study contributes by extending the internal audit literature through an integrated examination of moral courage and psychological capital within a public higher education context, an area that remains underexplored. It also advances Social Cognitive Theory by demonstrating the differentiated moderating role of ethical culture on personal psychological resources versus moral attributes. Practically, the findings provide insights for PTN BLU management to enhance internal audit effectiveness through the development of auditors’ psychological capital supported by a consistently internalized ethical culture.